Meridianins, a new family of protein kinase inhibitors isolated from the Ascidian Aplidium meridianum - Gompel, Marie (2004)
Meridianins are brominated 3-(2-aminopyrimidine)-indoles which are purified from Aplidium meridianum, an Ascidian from the South Atlantic (South Georgia Islands). We here show that meridianins inhibit various protein kinases such as cyclin-dependent kinases, glycogen synthase kinase-3, cyclic nucleotide-dependent kinases and casein kinase 1. Meridianins prevent cell proliferation and induce apoptosis, a demonstration of their ability to enter cells and to interfere with the activity of kinases important for cell division and cell death. These results suggest that meridianins constitute a promising scaffold from which more potent and selective protein kinase inhibitors could be designed.